Increased Occurrence of Mutant rtI233V of HBV in Patients Receiving Adefovir Therapy. Issue 1 (January 2016) - Liu, Yan; Xin, Shaojie; Ye, Xiaoling; Chen, Rongjuan; Xu, Zhihui; Li, Xiaodong; Ye, Haiyan; Cheng, Shuquan; Xu, Dongping
Background: The study aimed to clarify whether the rtI233V substitution affects adefovir (ADV) resistance. Methods: A total of 18, 419 patients from Beijing 302 Hospital were investigated. HBV complete reverse transcriptase region of the polymerase was screened by direct sequencing and verified by clonal sequencing if necessary. Replication-competent wild-type and mutant HBV genomic amplicons were transfected into HepG2 cells for phenotypic analysis of viral replication capacity and drug susceptibility. Results: The rtI233V substitution was detected in 38/5, 344 (0.71%) ADV-treated patients and in 8/13, 075 patients without receiving ADV ( P <0.001). Eight patients with rtI233V ± rtA181V/rtN236T had virological breakthrough in the clinical course of ADV treatment. Phenotypic analysis showed that rtI233V mutants from patient 1 and patient 2 exhibited 1.57-fold and 1.51-fold decreased susceptibility to ADV, respectively, compared to wild-type virus; by contrast, rtN236T and rtI233V+N236T mutants from patient 1 had 6.82-fold and 5.28-fold decreased susceptibility to ADV. rtI233V, rtN236T and rtI233V+N236T mutants had 97.5%, 30.2% and 69.7% of replication capacity compared to wild-type virus in the absence of antivirals and all remained susceptible to lamivudine, entecavir and tenofovir. Viral replication capacity correspondingly decreased after eliminating rtI233V from rtI233V+N236T mutant and was restored after introducing rtI233V into rtN236T mutant. In clinical practice, switching to entecavir rescue therapy suppressed HBV DNA to an undetectable level for both patients. Conclusions: rtI233V usually emerged in ADV-treated patients with little impact on ADV susceptibility but it effectively restored replication capacity of the rtN236T mutant, suggesting that rtI233V may partly serve as a compensatory mutation associated with ADV resistance.